Signaling in Credit Markets - Milde, Hellmuth; Riley, John G. (Quarterly Journal of Economics, 1988)
In this paper we show that, under a variety of alternative assumptions about the private information of loan applicants, a competitive market for loans is characterized by screening. Banks separate out loan risks by offering higher loans at higher interest rates. Depending on the nature of the informational asymmetry, it may be that applicants with less risky projects select larger rather than smaller loans. Comparative statics implications are also examined. In particular, we explore the effects of an increase in banks' cost of funds on average loan quality.